LEVEL OF CAPABILITY OF VILLAGE OFFICIALS IN CARRYING OUT GOVERNMENT ADMINISTRATION DUTIES IN HARAPAN VILLAGE, TANETE RIAJA DISTRICT, BARRU REGENCY - Rosdiana; Aminah, A.; Musdalifa (P3M Stia Al Gazali Barru and Meraja media, 2023)
[Full Paper] to pdf Copyright (c) 2023 Meraja journal